Uber, TaskRabbit and Co: platforms as employers? rethinking the legal analysis of crowdwork - Prassl, J; Risak, M (University of Illinois College of Law, 2016)
One of the key assumptions underpinning the rise of ‘crowdsourced work’ – from transport apps including Uber to online platforms such as Amazon’s Mechanical Turk – is the assertion put forward by most platforms that crowdworkers are self-employed, independent contractors. As a result, individuals might find themselves without recourse to worker-protective norms, from minimum wage and working time law to health and safety regulations and unfair dismissal protection. But is this account accurate? In this paper, we hope to challenge prevailing assumptions, arguing that in certain scenarios crowdworkers can, and should, be classified as workers within the scope of domestic employment law. The approach proposed, however, is an initially counterintuitive one: we advocate the adoption of a functional concept of the employer as a regulatory solution to crowdwork employment, with platforms, crowdworkers, and service users each shouldering their appropriate share of employer responsibilities